A bridge to progress further afield: The promise of a common framework on attentional capture. Issue 9 (21st October 2021) - Most, Steven B.; Curby, Kim M.
ABSTRACT: Although physical salience looms large in the attentional capture literature, stimuli can also capture attention via salience deriving from non-physical factors. Such psychological salience can stem, for example, from the emotional resonance of stimuli or their relevance to a person's expertise. We consider how insights from a recently proposed framework for attentional capture can be used to advance theory and drive research on the role of emotion-driven attentional biases in clinical disorders and on how attentional allocation changes with the development of perceptual expertise. In return, we wonder how their common framework can be enriched through considerations of psychological salience.